Online Food Purchasing Habit among the Hostel Students in Anand City, Gujarat, India - , Yash Vala; , Krunal C. Kamani; , Maulik C. Prajapati; , Mahendra D. Gurjar; , Ashish K. Makwana (Archives of Current Research International, 2025)
This research explores the online food delivery consumption patterns among college students in Anand City, focusing on the influence of area of residence (rural vs. urban) on purchasing behavior. Data collected from 100 respondents through a structured questionnaire reveals significant differences in frequency and preferences between rural and urban users. While awareness of online food delivery services is high (94%), urban respondents demonstrate a higher tendency for frequent purchases compared to rural counterparts, with weekly and monthly orders being more common in urban areas. Platforms like Swiggy and Zomato dominate the market, preferred for their reliability and variety, whereas other services see minimal usage. Fast delivery, discounts, and reasonable pricing emerge as key factors influencing purchase decisions. Despite growing acceptance, a significant portion of respondents still prefer cooking at home or dining out, primarily due to concerns about food quality, hygiene, and delivery costs. Payment preferences reveal a strong inclination toward digital payments, especially UPI, with cash on delivery remaining popular. Customer satisfaction is highest for Swiggy and Zomato, while other platforms lag behind. Respondents emphasize the need for improvements in delivery charges, food quality, and service speed to enhance the overall experience. The study highlights the evolving food consumption landscape in Anand, emphasizing the growing importance of online food delivery while underscoring challenges related to affordability, trust, and service quality.